The Impact of Millionaires’ Secret Strategy on Entrepreneurial Performance through Entrepreneurial Motivation - Zulkarnain, Kedah; Mohamad Asri, Abdullah; Md. Aftab, Anwar (2016)
The spotlight of this study is to examine the attributes and essential elements of millionaires’ secret strategy and to utilise a contemporary psychological method to evaluate consciousness that enhances entrepreneurial performance through entrepreneurial motivation among entrepreneurs in Malaysia. The premise of this point of convergence is to know which elements of a secret entrepreneurial strategy are deficient and to have the capacity to concoct thoughts that can be utilised to enhance these lacking for entrepreneurial success. The study represents a significant positive relationship between millionaires’ secret strategy and entrepreneurial performance mediated by entrepreneurial motivation. The findings of the results also confirm that millionaire’s secret strategy is an important factor among other factors that have influenced over entrepreneurial motivation. The outcomes of the study will help the training and development authorities to take necessary steps to outline new and productive contents for potential entrepreneurial development.